Investigating ITM2B‐associated ataxia in a Taiwanese cerebellar ataxia cohort - Shih‐Yu Fang; Cheng‐Tsung Hsiao; Kang‐Yang Jih; Yu‐Sheun Tsai; Kuan‐Lin Lai; Cheng‐Ta Chou; Yi‐Chu Liao; Yi‐Chung Lee (Annals of Clinical and Translational Neurology)
Abstract Objective The genetic causes of a significant number of patients with cerebellar ataxia remain unsolved. Variations in the ITM2B gene, typically linked to dominantly inherited dementia, can sometimes present with cerebellar ataxia as an early symptom. This study aims to investigate the role of ITM2B variations in a Taiwanese cohort with unsolved cerebellar ataxia. Methods Genetic analysis of ITM2B was performed in 212 unrelated Taiwanese patients with unsolved cerebellar ataxia. Eight short tandem repeat markers flanking ITM2B were genotyped to analyze the associated haplotype. Affected carriers underwent comprehensive clinical evaluations. Results A heterozygous ITM2B variant, c.800G>T (p.(Ter267LeuextTer11)), was identified in three patients. Haplotype analysis demonstrated a shared haplotype linked to this variant in the three families, suggesting a founder effect. The three probands and additional three affected relatives presented with cerebellar ataxia and unsteady gait with an average onset age of 43.2 years. Most participants had no cognitive impairment at symptom onset but experienced memory decline, oculomotor disturbances, lower limb spasticity, and extensor plantar responses within 2–5 years. Magnetic resonance imaging and spectroscopy revealed progressive extension of white matter hyperintensity over periventricular and subcortical regions, subtle hippocampal atrophy, preserved cerebellar volumes, and decreased N‐acetylaspartate/creatine ratio over the vermis. Interpretation ITM2B mutations accounted for 1.4% of cerebellar ataxia cases in the Taiwanese cohort, with patients carrying ITM2B c.800G>T descending from a common ancestor. This study underscores the importance of considering ITM2B variations as a potential cause of cerebellar ataxia, even in the absence of dementia at the initial presentation.